An Experimental Investigation On Converting Conventional to Supercharged CI Engine - N., Balaji Ganesh; P.V, Sri Hari (International Journal of Integrated Engineering, 2023)
Due to the increase in grounds performance of internal combustion engines, the diesel engine has become dominant forces in the power, propulsion, and energy. For domestic, industrial, and transportation applications, internal combustion engines are the more reliable and misogynist power source. Diesel engines rely on fluid Spritz dynamics for air-fuel mixtures and swirl plays a crucial role in the pattern of air motion as impacts fuel air mixing and combustion. Further-more, older studies have indicated that it affects heat transfer, combustion efficiency, and engine emissions. By varying air inlet pressure, this work demonstrates the presentation and production features of Compression Ignition engines. Using compressor, the inlet pressure of air is manipulated, and when compressed air is sent to engine at different pressures, performance parameters and heat balance sheets are calculated.